Notice of meeting - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
806-0004-001 PEOPLE AND FREEDOM GROUP The next meeting of the Group will be held (by kind invitation of Dr. Fairfield) on Wednesday, March 29th, at 8.15 p.m. at 1, Raymond Buildings, Grays Inn. (Chancery Lane tube station). Senor LIZASO, head of the Basque Delegation, will speak on GERMANY AND THE BASQUE COUNTRY, and will also touch on the special problems of the Basque refugees. It is hoped that all members will make a special effort to attend. B. Barclay Carter, Hon. Sec. 32, Chepstow Villas, W.11 292C/806.1/1/4